PHYTOTOXIDITY AND GREEN COVERAGE OF BERMUDA LAWN SUBMITTED TO NITROGEN AND GLYPHOSATE DOSAGES - Begueline, Maria Clara Lelles Moreira [UNESP]; Alfonsi, Leandro Garcia [UNESP]; Assis, Kamila Cristina de Credo [UNESP]; de Godoy, Leandro José Grava [UNESP]; Costa, João Victor [UNESP] (My University, 2021)
The present work had as objective to evaluatedosages of glyphosate and nitrogen in the rate of green cover and in the rate of phytotoxicity by image of Bermuda lawn in tropical conditions. A completely randomized design with six replications was adopted. The treatments were done in a 4 x 4 factorial scheme, with four sub-doses of glyphosate (0, 200, 400 and 600 g ha-1 of ia), and four doses of nitrogen (0, 25, 50 and 100 mg dm-3). The nitrogen was performed manually at 27 days after planting (DAP), with 100 ml of water solution with urea, in the doses of 0, 167, 333 and 667 mg for each 100 ml of water. The glyphosate underdose was performed with a manual pressure sprayer with a working pressure of 45 psi. The herbicide used was Roundup transorb, with i.a (glyphosate) of 480 g L-1. The percentages of phytointoxication were determined by digital images according to the green coverage rate methodology. The green coverage rate and the phytotoxicity rate were evaluated with the aid of the Corew Draw® imaging software. It was concluded that the sub-dose of glyphosate that best suited as a growth regulator was 432 g ha-1 with doses of 100 mg dm-3 of nitrogen for a better quality of the lawn. The application of glyphosate is feasible in the growth control of the Bermuda lawn as long as it presents an efficient fertilization in Nitrogen. The addition of nitrogen dosages provides further development of the Bermuda lawn.
FITOTOXICIDAD Y TASA DE COBERTURA VERDE DE GRAMADO BERMUDA SOMETIDO A DOSIS DE NITRÓGENO Y GLIFOSATO
FITOTOXIDEZ E TAXA DE COBERTURA VERDE DE GRAMADO BERMUDA SUBMETIDO A DOSAGENS DE NITROGÊNIO E GLIFOSATO
Keywords: Bermuda-grass; Fertilizing; Growth regulator; Lawn Nutrition